ABRAHAMIC TRADITIONS AND ECOLOGICAL RESPONSIBILITY: PATHWAYS TO INTERFAITH HARMONY AND ENVIRONMENTAL RESILIENCE IN PAKISTAN (Al-Aasar, 2025)
Pakistan faces an escalating environmental crisis, characterized by rising temperatures, melting glaciers, floods, water scarcity, deforestation, pollution, and biodiversity loss. These challenges disproportionately affect vulnerable populations, underscoring the need for ethically grounded, inclusive, and practical responses. This paper examines how the Abrahamic faiths Judaism, Christianity, and Islam provide a robust ethical and spiritual foundation for environmental stewardship. Across these traditions, creation is sacred, and humans are entrusted as stewards rather than owners, accountable for maintaining balance, preventing waste, and protecting all life. Judaism emphasizes principles such as Shomrei Adamah, Bal Tashchit, and Tikkun Olam; Christianity highlights stewardship, care for creation, and reconciliation; Islam advocates Tawhid, Khilafah, Mizan, Israf, and Hisab.The study also explores the critical role of Pakistan’s Ministry of Climate Change (MoCC) in promoting sustainable development through initiatives and how these programs can be enhanced through faith-based engagement. Religious leaders and faith-based organizations (FBOs) possess moral authority and grassroots networks capable of mobilizing communities, fostering environmental awareness, and translating ethical principles into practical action. Interfaith collaboration can further strengthen social cohesion, environmental justice, and national solidarity.By integrating religious ethics with governmental policy and community action, Pakistan can address environmental degradation not merely as a technical or political challenge but as a moral and spiritual imperative. The paper concludes with recommendations for faith-based education, community mobilization, sustainable investments, policy advocacy, capacity building, and protection of vulnerable populations, demonstrating that ecological stewardship is a shared responsibility across faiths and a catalyst for sustainable development.